The Jurisprudence of Crimes against Humanity and Global Poverty - Ogbe, Richard Suofade (ABUAD Law Journal, 2023)
There have been efforts at evaluating the causes of global poverty vis a vis crime against humanity. The gap between rich and poor has increased over the years in the world. Crime against humanity is an offense in international criminal law that comprises various acts such as murder, extermination, enslavement, torture, forcible transfers of populations, imprisonment, rape, persecution, enforced disappearance, and apartheid, among others. States are obligated to guarantee the welfare and security of their citizens by carrying out programmes meant to eradicate poverty. Many states in the world have failed in this regard. The conversation as to whether global poverty can be taken as a crime against humanity appears to be mere rhetoric. This paper seeks to argue that there are cogent reasons why global poverty should be taken as a crime against humanity because poverty makes people sick, and dehumanizes the human person. This is particularly based on the standard and guidelines adopted in defining crimes against humanity as encapsulated in international laws, especially the Rome Statute of the International Criminal Court and International Military Tribunal for the former Yugoslavia. This paper submits that the causes of global poverty are comparable with the crimes of slavery, torture, murder, etc because poverty in itself is a massive crime against humanity. The international community must hold to account the few privileged and rich persons whose economic activities perpetuate poverty in the world and treat them in the same way the perpetrators of rape, torture, enslavement, murder, and extermination are treated. This is a sure way the global poor's right to good and meaningful life can be guaranteed. The international community should continue to protect the poor from the horrible institutions and poverty inflicted upon them by the few rich and privileged persons in the world. This paper, therefore, seeks to conceptually clarify the connection between poverty and human rights from an international human rights law perspective.